Production and Antimicrobial Activity of Nisin Under Enological Conditions - Fernández-Pérez, Rocío; Sáenz, Yolanda; Rojo-Bezares, Beatriz; Zarazaga, Myriam; Rodríguez, Juan M.; Torres, Carmen; Tenorio, Carmen; Ruiz-Larrea, Fernanda (Frontiers in Microbiology, 2018)
Lactic acid bacteria (LAB) are responsible for the malolactic fermentation of wines, and, therefore, controlling the growth of these bacteria is a key factor for elaborating premium wines. Sulphur dioxide has been traditionally used as an efficient antimicrobial and antioxidant agent, however, nowadays consumers' demand tends towards a reduction of sulphur dioxide levels in wine and other fermented foods. A previous study of our research group had demonstrated the effectiveness of the bacteriocin nisin to inhibit the growth of enological LAB, and its activity had been tested in culture broths. The aim of this study was to investigate the possibility of controlling the growth of bacteria in wine by the use of nisin in combination with sulphur dioxide, and to study nisin production by the natural producer Lactococcus lactis LM29 under enological conditions. Our results showed that L. lactis LM29 produced nisin in the presence of 2 % and 4 % ethanol (v/v), while higher concentrations of ethanol fully inhibited the production of nisin. We obtained a nisin enriched active extract (NAE) from the cell-free supernatant of a culture of L. lactis LM29 in MRS broth containing 60 % (v/v) sterile grape juice, and the extract was fully active in inhibiting the growth of the enological LAB tested by the microtiter method. Moreover, the nisin concentration of the obtained NAE could actually prevent the formation of an undesirable biofilm of LAB strains. Finally, our results of wine ageing under winery conditions showed that the use of 50 mg/L nisin decreased 4-fold the concentration of sulphur dioxide required to prevent LAB growth in the wines.